Spatiotemporal characteristics of macroinvertebrate functional feeding groups and biological assessment of water quality in the Hulan River Basin - Peilun Li; Shuhan Xiong; Jiacheng Liu; Xiangsheng Meng; Anqi Wang; Chunfeng Wang; Yanshen Zhang; Jilong Wang (Global Ecology and Conservation)
In order to evaluate the health of river ecosystems, it is essential to look at how macroinvertebrates are affected by changes in their habitat and how they react to environmental influences. This study focused on the Hulan River Basin, situated in a cold region, utilizing survey data on macroinvertebrates and water environmental factors collected in late April, late June, and late September of 2023. The research thoroughly analyzed the spatiotemporal distribution characteristics of macroinvertebrate functional feeding groups (FFGs) and their correlations with aquatic environmental factors, subsequently conducting a comprehensive biological assessment of water quality. The results indicated the collection of 88 taxonomic units (genus or species) of macroinvertebrates, belonging to 4 phyla, 14 orders, and 35 families. Among these, collector-gatherers were the most prevalent FFG, followed by scrapers, predators, and collector-filterers, with shredders being the least represented. Distinct seasonal variations in dominant macroinvertebrate species were observed, with Chironomus sp. being the annual dominant among collector-gatherers and Semisulcospira amurensis among scrapers. The PERMANOVA test revealed significant differences in the densities of macroinvertebrate FFGs between different river sections and highly significant differences between months. Redundancy Analysis (RDA) indicated that the influential environmental factors varied by month, with water temperature, dissolved oxygen, and total phosphorus being significant in April; ammonia in June; and dissolved oxygen, pH, and alkalinity in September. The ecosystem assessment of the Hulan River Basin based on FFG parameters showed that the upstream possesses robust capabilities for material cycling, longitudinal matter transport, and coastal material input, with the highest habitat stability. Temporally, parameters such as longitudinal transport capacity peaked in September, coinciding with the strongest habitat stability. The Hilsenhoff Biological Index and Shannon-Wiener Index assessments indicated water quality ranging from good to excellent in the upstream, moderate in the midstream, and moderate to poor in the downstream. Overall, the water quality in the upstream areas was superior to that in the midstream and downstream. This study demonstrates that macroinvertebrate FFGs are highly sensitive to human activities and agricultural pollution in the midstream and downstream areas of the Hulan River Basin. These findings provide valuable insights for the restoration of river ecosystems.